STRATEGI MANAJEMEN PERUBAHAN DALAM ADOPSI TEKNOLOGI BARU DI PELAYANAN KEBIDANAN - Sri Rahma Friani; Meli Safreni Turnip; Adventides Natali Siahaan (Politeknik Ganesha Medan, 2023)
The adoption of new technologies in obstetric care, such as electronic medical record (EMR) systems, advanced diagnostic tools, or tele-obstetric platforms, has significant potential to improve the efficiency, accuracy, and accessibility of care. However, the implementation of new technologies is often accompanied by resistance, organizational culture challenges, and operational complexity, necessitating effective change management strategies. This literature review examines relevant change management models and principles, identifies key strategies to facilitate the adoption of new technologies in obstetric settings, and analyzes enabling and inhibiting factors. The goal is to provide insights for health facility managers, midwives, and policymakers in planning and implementing successful technology initiatives, which will ultimately improve the quality and innovation of obstetric care